Associations between nausea and vomiting in pregnancy, disgust sensitivity, and first-trimester maternal serum free β-hCG and PAPP-A - Kaňková, Šárka; Hlaváčová, Jana; Roberts, Kateřina; Benešová, Jana; Havlíček, Jan; Calda, Pavel; Dlouhá, Daniela; Roberts, S Craig (Hormones and behavior, 2023)
Elevated levels of nausea and vomiting in pregnancy (NVP) and disgust sensitivity have been observed in the first trimester and both are thought to have a protective function for the mother and her fetus. Their aetiology is not clear, however, with previous studies attributing elevated NVP and disgust to various factors including endocrine changes, immunological changes, and psychological variables. To date, no study has directly assessed the relationship between disgust and NVP. Here, we prospectively collected two independent samples (S1 and S2; n1 = 201, n2 = 391) of women in the first trimester of pregnancy, who completed the Index of Nausea, Vomiting, and Retching and the Disgust Scale-Revised. We also measured free β-human chorionic gonadotropin (hCG) and pregnancy-associated plasma protein A (PAPP-A) in maternal serum. Our results did not confirm any association between NVP and disgust; in addition, they indicate that NVP and disgust may have different proximate causes. Disgust sensitivity was significantly negatively correlated with free β-hCG and (only in S1) with PAPP-A. In contrast, NVP was significantly positively associated with free β-hCG levels and (only in S1) with PAPP-A. While low hCG levels seem to be an important indicator for activation of the behavioral immune system in the first trimester, increased hCG levels play a role in stronger symptoms of NVP, a result consistent with previous studies. Levels of PAPP-A are likely part of a larger network of immunological and endocrine responses and do not appear to provide sufficient information for predicting women's NVP and disgust sensitivity.
Keywords: Pregnancy-Associated Plasma Protein-A; Female; PAPP-A; biologické markery; NVP; Rhodes index; Biomarkers; Chorionic Gonadotropin, beta Subunit, Human; ženské pohlaví; lidé; Parity; Free β-hCG; těhotenství; Pregnancy Trimester, First; Anxiety; Vomiting; nauzea; Nausea; odpor; zvracení; komplikace těhotenství; první trimestr těhotenství; Compensatory prophylaxis hypothesis; Pregnancy Complications; lidský choriogonadotropin, beta podjednotka; Pregnancy; těhotenský plazmatický protein A; Disgust; Humans